An investigation on the effects of financial management practices on firm’s financial performance: a case study of Zimbabwe Power Company. - Tabona, Jonathan Stalon (Midlands State University, 2020)
The study focused on the effects of financial management practices on the firm’s financial performance. This study was motivated by the decline in the profitability of the organisation despite the company making effort to implement cost cutting measures. As a result, the study investigated the effect of current practices in the areas of working capital management, non-current assets management and investment practices. The study made use of descriptive research design as to allow quantitative analysis. The data collected was presented using graphs, tables and percentages. Regression analysis and Pearson coefficient of correlation was used to establish the relationship between the financial performance and financial management practices variables in the study. Correlation analysis shows that financial performance has a strong negative relationship with working capital management of -0.6722, a moderate negative relationship with investment practices of -0.5646 and a weak negative relationship with non-current assets management practices of -0.4027. The coefficient of determination (R-square) indicated that 99.87% of variation in financial performance is explained by changes in financial management practices. It was found that the financial management practices have a significant effect on the financial performance of Zimbabwe Power Company. The study recommended improvement in the areas of accounts receivables management and asset performance management to ensure efficiency in the utilisation of resources. In order to improve implementation of effective financial management practices the study recommended improvement in communication and training of employees at all levels.